2018
DOI: 10.18203/2349-3291.ijcp20181387
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and diagnostic features of dengue haemorrhagic fever in children

Abstract: Background: Diagnosis of dengue hemorrhagic fever (DHF) in children is based on clinical suspicion and prompting laboratory criteria.Methods: This prospective study in children (6 months-14 years) presenting with features of DHF aimed to identify symptoms and signs, laboratory parameters for in early detection and assessed the association between clinical, laboratory, immunological parameters and outcome.Results: Of 50 children, 26 were females, mean±SD age was 8.3±3.02 years; age group 8-12 years were affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(15 reference statements)
3
2
0
Order By: Relevance
“…Considering presenting symptoms next to fever (72.55%), headache (52.94%), vomiting (41.18%), myalgia (37.25%) and hemorrhagic manifestations (21.57%) were commonly found in this study. Reddy GC et al 12 in their study found fever as most common symptom, followed by skin rash (56.0%), myalgia (52.0%) and head ache (48.0%) were the symptoms which is little bit different from this study but our findings were similar to study of Kumar A et al 13 Abdominal pain and vomiting were also common presenting symptom in this study which may often lead to a delay in the diagnosis of dengue. 14 Deranged liver operate in dengue fever infection is a result of the direct impact of the virus on liver cells or the unregulated host response against the virus may cause fulminant hepatic failure from acute hepatitis and massive necrosis of the liver, causing hepatic encephalopathy and even death.…”
Section: Discussionsupporting
confidence: 83%
“…Considering presenting symptoms next to fever (72.55%), headache (52.94%), vomiting (41.18%), myalgia (37.25%) and hemorrhagic manifestations (21.57%) were commonly found in this study. Reddy GC et al 12 in their study found fever as most common symptom, followed by skin rash (56.0%), myalgia (52.0%) and head ache (48.0%) were the symptoms which is little bit different from this study but our findings were similar to study of Kumar A et al 13 Abdominal pain and vomiting were also common presenting symptom in this study which may often lead to a delay in the diagnosis of dengue. 14 Deranged liver operate in dengue fever infection is a result of the direct impact of the virus on liver cells or the unregulated host response against the virus may cause fulminant hepatic failure from acute hepatitis and massive necrosis of the liver, causing hepatic encephalopathy and even death.…”
Section: Discussionsupporting
confidence: 83%
“…There were similar findings in studies by Malleshappa K, et al 20 , Arora SK, et al 19 and Reddy A, et al 13 . Respiratory distress was significantly associated with SD which was similar to studies by Reddy A, et al 13 , Naaraayan SA, et al 21 and Reddy GC, et al 22 . It might be due to plural effusion or pulmonary oedema.…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings were seen in the study by Afroze S, et al 15 . On chest xray, bilateral pleural effusion was associated with SD, which was similar to the study by Reddy GC, et al 22 , On USG of abdomen, ascites was the common finding associated with SD. There was a similar finding in the study by Pothepragada S, et al 25 on univariate analysis.…”
Section: Discussionsupporting
confidence: 88%
“…In another study done by Reddy GC et al; [16] found that the anorexia (81.0%), nausea/vomiting (7 9 .0%), headache (5I.4%) and bleeding tendency were common features. In comparison to adults, apart from these symptoms, positive tourniquet test, abdominal tenderness, convalescent rash, pleural effusion and ascites due to plasma leakage as a result of low serum albumin and sodium were also reported and further showed a higher association of bleeding in children, but requirement of transfusion was more in adults compared to children [17] .…”
Section: Discussionmentioning
confidence: 98%